(untitled) (Research, Society and Development, 2022)
Anxiety disorders are the most prevalent group of psychiatric pathologies. Within the context of new therapies for anxiety, phytotherapy has stood out positively. Thus, this review aims to study the action of Silexan in anxiety disorders, based on the Hamilton Anxiety Scale (HAM-A), making a parallel with other anxiolytic drugs of well-defined use in psychiatry. This is an integrative review type research, which included clinical trials with human beings. The search was carried out through online access to the databases PUBMED, SciELO, LILACS, Scopus, Web of Science, and Science Direct. The strategy for selection of articles followed the steps: search of the selected databases, reading of the title and abstract of all articles and exclusion of those that did not address the review topic, critical reading of the articles in full, and exclusion of those that did not meet the inclusion criteria. Thus, a total of 5 articles were selected. In all clinical trials, the use of Silexan showed higher response and remission rates compared to other interventions. Thus, it can be concluded that Silexan has some effectiveness in controlling anxiety. However, this study has limitations in that the included studies varied in number of participants, patient health status, and comparison. In addition, it would be interesting to test the use of Silexan in higher doses, making a comparison with the use of anxiolytic drugs in therapeutic doses already consolidated.